Fortæller du mig? Viden om venskab i litteratur og videnskab - Emmeche, Claus (Passage - Tidsskrift for litteratur og kritik, 2018)
Claus Emmeche: “Do You Tell Me? Knowledge about Friendship in Literature and Scholarship” Friendship as an interpersonal relation is discussed through the perspective of history of knowledge as a historically contingent relation that can be modelled in fiction, literature, and different academic disciplines, like for instance philosophy, anthropology, and history. The opposing claims of philosopher Alexander Nehamas and literary critic Gregory Jusdanis on the adequacy of the novel to describe friendship is discussed, partly drawing on literary friendship studies by Janet Todd and Victor Luftig. Starting from the Neapolitan Novels by Elena Ferrante (depicting a difficult, close, life-long friendship between two women and the precarious knowledge emerging from this relationship) and recent scholarship on Ferrante’s work, the article shows how these novels are not just inspired by but also comment critically upon the work on narrative friendship by philosopher Adriana Cavarero.